Dunia Boneka, Ribuan Kata: Mengungkap Peran Permainan Boneka Dalam Pengembangan Kosakata Dan Kemampuan Berbicara Anak - Arif Rifa’i; Dwi Andayani; Indri Vitriani; Saifuddin Helmi; Indah Lestari; Mochamad Widjanarko (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
This study aims to reveal the role of puppet play in the development of vocabulary and speaking skills of early childhood. Using a qualitative approach with a case study method at Pertiwi Kindergarten, Dadirejo Village, the study involved five children aged 5–6 years and two class teachers. Data were collected through participant observation, in-depth interviews, and documentation, then analyzed thematically. The results showed that puppet play created a fun, safe learning atmosphere, and stimulated children to speak more actively and variedly. Children not only increased their vocabulary, but also improved their ability to construct complex sentences, use adjectives, conjunctions, and more complete narrative structures. In addition, puppet play facilitated social interactions that strengthened children's pragmatic and emotional expression skills. These findings support the theory of language development based on social interaction and show that puppet play is an effective, inexpensive, and easy-to-implement pedagogical strategy. Thus, puppet play can be used as a strategic alternative in the development of early childhood language, both in school and home environments